Competitive Moment Matching of a New-Keynesian and an Old-Keynesian Model - Reiner Franke (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
The paper considers two rival models referring to the new macroeconomic consensus: a standard three-equations model of the New-Keynesian variety and dynamic adjustments of a business and an inflation climate in an `Old-Keynesian' tradition. Over the two subperiods of the Great Inflation and Great Moderation, both of them are estimated by the method of simulated moments. An innovative feature is here that it does not only include the autocovariances up to eight lags of quarterly output, inflation and the interest rate, but optionally also a measure of the raggedness of the three variables. In short, the performance of the Old-Keynesian model is very satisfactory and similar to, unless better than, the New-Keynesian model. In particular, the Old-Keynesian model is better suited to match the new moments without deteriorating the original second moments too much.
Keywords: C52; E32; E37; 330